2012
DOI: 10.1002/adma.201200924
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Printed Transistors Realized Using Femtoliter Gravure‐Printed Sub‐10 μm Metallic Nanoparticle Patterns and Highly Uniform Polymer Dielectric and Semiconductor Layers

Abstract: COMMUNICATION Adv. Mater. 2012, 24, 3065-3069 using an Agilent 4156C semiconductor parameter analyzer. A standard f T measurement setup was used with a high impedance active probe, Picoprobe Model 18C with 20 fF input capacitance by GGB Industries Inc. to minimize coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
175
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 20 publications
4
175
1
Order By: Relevance
“…Recent studies have reported on OTFT devices fabricated entirely or partially with printing methods such as gravure printing, transfer printing, and inkjet printing. [6][7][8][9][10][11][12][13][14][15][16][17][18] However, the spatial resolution of these printing methods above is in the range of 10-100 µm, [19] which is not fine enough to fabricate short-channel high-speed OTFTs. Reverse offset printing is a unique method providing for high-resolution features, submicron in scale.…”
Section: Doi: 101002/aelm201700313mentioning
confidence: 99%
“…Recent studies have reported on OTFT devices fabricated entirely or partially with printing methods such as gravure printing, transfer printing, and inkjet printing. [6][7][8][9][10][11][12][13][14][15][16][17][18] However, the spatial resolution of these printing methods above is in the range of 10-100 µm, [19] which is not fine enough to fabricate short-channel high-speed OTFTs. Reverse offset printing is a unique method providing for high-resolution features, submicron in scale.…”
Section: Doi: 101002/aelm201700313mentioning
confidence: 99%
“…98 Kang et al, for example, utilize an optimized microgravure process to print silver patterns and poly(4-vinyl phenol) (PVP) dielectric layers. 99 A transistor with record transition frequencies of >300 kHz was achieved with a spin-coated organic semiconductor poly(2,5-bis(3-alkythiophen-2-yl)thieno [3,2-b] thiophene) (pBTTT).…”
Section: Thin Film Transistorsmentioning
confidence: 99%
“…Only a handful of reports on OFET alternating current (AC) characterization use fabrication techniques that even partially fulfi l the requirements set out above. [12][13][14][15][16][17][18][19][20][21][22][23] However to build functional fl exible circuits it is important to understand how to reconcile device fabrication and performance. [24][25][26] This is a requirement if plastic electronics are to be implemented in applications such as radio frequency identifi cation (RFID) tags which operate at megahertz frequencies.…”
Section: Doi: 101002/aelm201500024mentioning
confidence: 99%